2012
DOI: 10.1007/s10194-012-0424-y
|View full text |Cite
|
Sign up to set email alerts
|

Migraine in women: the role of hormones and their impact on vascular diseases

Abstract: Migraine is a predominantly female disorder. Menarche, menstruation, pregnancy, and menopause, and also the use of hormonal contraceptives and hormone replacement treatment may influence migraine occurrence. Migraine usually starts after menarche, occurs more frequently in the days just before or during menstruation, and ameliorates during pregnancy and menopause. Those variations are mediated by fluctuation of estrogen levels through their influence on cellular excitability or cerebral vasculature. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
189
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(209 citation statements)
references
References 135 publications
(169 reference statements)
9
189
0
8
Order By: Relevance
“…While an association between migraine and stroke has not been confirmed in migraine-without-aura patients, 97 the risk of both ischemic and hemorrhagic 98 stroke is two to three times higher in migraine-with-aura patients. There may, however, be other more profound vascular risks present in these patients who were not accounted for in the studies.…”
Section: Migraine As Risk Factor For Strokementioning
confidence: 98%
“…While an association between migraine and stroke has not been confirmed in migraine-without-aura patients, 97 the risk of both ischemic and hemorrhagic 98 stroke is two to three times higher in migraine-with-aura patients. There may, however, be other more profound vascular risks present in these patients who were not accounted for in the studies.…”
Section: Migraine As Risk Factor For Strokementioning
confidence: 98%
“…This risk may further increase when combined oral contraceptives (COCs) are used for the prevention of pregnancy (4)(5)(6)(7). The cardiovascular risk of COCs, which contain ethinylestradiol and a synthetic progestin, has been mainly attributed to the oestrogen component which exerts a strong effect on the coagulation system.…”
Section: Introductionmentioning
confidence: 98%
“…It has been postulated that the differing ability to metabolize estrogen as well as the existence of polymorphism in the genes encoding for sex hormones, their receptors, or metabolites of the hormonal pathways may be responsible for this differences in presentation and symptomatology during pregnancy. 20 For example, Colson et al 21 found a correlation between the polymorphism in progesterone receptors and the incidence of migraine.…”
Section: Discussionmentioning
confidence: 99%